Dietary Pediococcus acidilactici improves the intestinal functions by regulating the expression of intestinal inflammatory genes and intestinal microbiota in aged laying hens at 80–91 weeks of age - Dong, Airong; Ding, Xuemei; Wang, Jianping; Zeng, Qiufeng; Bai, Shiping; Liu, Yan; Xuan, Yue; Li, Shanshan; Mu, Yadong; Peng, Huanwei; Zhang, Keying (Frontiers in Microbiology, 2025)
IntroductionPediococcus acidilactici CNCM I-4622 (PA) is a homofermentative Gram-positive coccus that produces lactic acid as a major metabolic by-product. However, the potential of PA to improve intestinal function and, as a result, improve production performance and quality in aged laying hens remains unclear. This study aimed to investigate the effects of PA on egg production, egg quality, intestinal health, and cecal microbiota in aged laying hens.MethodsA total of 180 Lohmann pink laying hens, aged 80 weeks, were randomly assigned to five groups and fed either a basal diet (PA0) or basal diets supplemented with PA at concentrations of 50, 100, 150, and 200 mg/kg (PA50, PA100, PA150, and PA200).ResultsCompared to the PA0 group, PA did not have a significant effect on the production performance of laying hens (p > 0.05). However, the content of diamine oxidase and the expression level of IL-8 mRNA in the PA50, P100, P150, and P200 groups were significantly reduced (p < 0.05). Additionally, the ileal villus height was significantly increased (p < 0.05). The cecal chowder pH and ileal crypt depth were also significantly lower (p < 0.05), while lipase activity in the ileal mucosa of the PA50 group was significantly increased compared to the PA0 group (p < 0.05). Furthermore, the expression of INF-γ and TNF-α mRNA in the jejunal mucosa was significantly down-regulated (p < 0.05), whereas the expression of Claudin mRNA was significantly up-regulated (p < 0.05). Notably, the relative abundance of Bacteroidota, Fusobacteriota, and Fusobacterium in the PA50 group was significantly higher than that in the PA0 group (p < 0.05).DiscussionAdditionally, cecal metabolomic analysis indicated that following the addition of PA, the pathways enriched with differential metabolites were primarily related to arginine and proline metabolism. Therefore, PA has the potential to improve intestinal morphology and flora, mitigate intestinal inflammatory factors, and strengthen intestinal barrier function. These benefits are attributed to the modulation of arginine and proline metabolic pathways, with optimal effects observed at an addition of 50 mg/kg.